Mannose-binding lectin levels and MBL2 gene polymorphisms are associated with dengue infection in Brazilian children at the early ages. (April 2022) - Sena, Marília A.; da Silva Castanha, Priscila Mayrelle; Giles Guimarães, Ana Beatriz; Oliveira, Paula Alexandra dos Santos; da Silva, Maria Almerice Lopes; Cordeiro, Marli Tenório; Moura, Patricia; Braga, Cynthia; Vasconcelos, Luydson Richardson Silva
Highlights: The MBL2 -221 (X/YX) variant was associated with greater risk of DENV infection. The LXPA haplotype, related to lower MBL levels, was exclusively found in dengue cases. The frequency of MBL2 structural variants (O/AO) were higher in DENV-naïve children. Serum levels of total and functional MBL were lower among DENV-infected children. Abstract: Background: The mannose-binding lectin (MBL) plays an important role in innate immunity. Genetically determined variations in serum levels of MBL may influence the susceptibility and clinical outcome of dengue infection in early life. Methods: We investigated the MBL2 gene polymorphisms and serum levels of MBL (total and functional) in children with asymptomatic (n=17) and symptomatic (n=29) primary dengue infections and age-matched uninfected children (n=84) enrolled in a birth cohort with dengue in Brazil. Polymorphisms of the MBL2 gene were assessed by reverse transcription-polymerase chain reaction (RT-PCR), whereas the enzyme-linked immunosorbent assay (ELISA) was used to quantify serum levels of MBL. Results: We found that the X allele and YX genotype in the MBL2 were more frequent in the dengue cases than in the control group. Likewise, the LXPA haplotype was exclusively found in dengue cases, thus probably related to dengue infection in our setting. Moreover, we found a higher frequency of the O allele and AO genotype in the control group. Serum levels of total and functional MBL were higher in dengue naïve infants than in dengue cases. Conclusions: MBL2 variants related to lower production of serum MBL were associated with dengue infection in infants, whereas intermediate to high levels of total and functional serum MBL were associated with protection against dengue infection. These findings highlight the role of MBL2 variants and serum levels of MBL in the susceptibility of children to dengue disease at early ages.